Click with a boronic acid handle: a neighboring group-assisted click reaction that allows ready secondary functionalization. Issue 82 (1st September 2015) - Draganov, Alexander B.; Wang, Ke; Holmes, Jalisa; Damera, Krishna; Wang, Danzhu; Dai, Chaofeng; Wang, Binghe
Abstract : A novel boronic acid facilitated cyclization reaction was developed. This reaction reaches completion at room temperature within minutes and is suitable for coupling and bioconjugation chemistry. Abstract : The feasibility of a neighboring boronic acid-facilitated facile condensation of an aldehyde is described. This reaction is bio-orthogonal, complete at room temperature within minutes, and suitable for bioconjugation chemistry. The boronic acid group serves the dual purpose of catalyzing the condensation reaction and being a handle for secondary functionalization.